Effect of a reduced fat and sugar maternal dietary intervention during lactation on the infant gut microbiome - Sindi, Azhar S.; Stinson, Lisa F.; Lean, Soo Sum; Chooi, Yit-Heng; Leghi, Gabriela E.; Netting, Merryn J.; Wlodek, Mary E.; Muhlhausler, Beverly S.; Geddes, Donna T.; Payne, Matthew S. (Frontiers in Microbiology, 2022)
Literature has shown that maternal diet during pregnancy is associated with infant gut bacterial composition. However, whether maternal diet during lactation affects the exclusively breastfed infant gut microbiome remains understudied. This study set out to determine whether a two-week of a reduced fat and sugar maternal dietary intervention during lactation is associated with changes in the infant gut microbiome composition and function. Stool samples were collected from four female and six male (n=10) infants immediately before and after the intervention. Maternal baseline diet from healthy mothers aged 22 to 37 was assessed using 24-hour dietary recall. During the two-week dietary intervention, mothers were provided with meals and their dietary intake was calculated using FoodWorks 10 Software. Shotgun metagenomic sequencing was used to characterise the infant gut microbiome composition and function. In all but one participant, maternal fat and sugar intake during the intervention were significantly lower than at baseline. The functional capacity of the infant gut microbiome was significantly altered by the intervention, with increased levels of genes associated with 28 bacterial metabolic pathways involved in biosynthesis of vitamins, amino acids, carbohydrates, and fatty acids and lipids. Although the dietary intervention did not affect the bacterial composition of the infant gut microbiome, relative difference in maternal fibre intake was positively associated with increased abundance of genes involved in biosynthesis of storage compounds, such as cyanophycin. Relative difference in maternal protein intake was negatively associated with Veillonella parvula, while positively associated with Klebsiella michiganensis. Relative difference in maternal sugar intake was positively associated with Lactobacillus paracasei. Relative difference in maternal fat intake was positively associated with genes involved in the biosynthesis of storage compounds, fatty acid and lipid, and metabolic regulator metabolic pathways. Conclusion: This pilot study demonstrates that a short-term maternal dietary intervention during lactation can significantly alter the functional potential, but not bacterial taxonomy, of the breastfed infant gut microbiome. While the overall diet itself was not able to change the composition of the infant gut microbiome, changes in intakes of maternal protein and sugar during lactation were correlated with changes in the relative abundances of certain bacterial species.